Empowering women on screen: exploring the influence of female protagonists on contemporary culture and gendered enjoyment in film - Fokiya Akhtar; Azmat Rasul (Cogent Arts & Humanities)
A prevalent notion in the film industry across the globe suggests that female-led films may underperform, leading producers to avoid casting women as leads. This fear of alienating male audiences perpetuates patriarchal ideologies, objectifies female bodies, reinforces gender stereotypes, and alters perceptions of femininity. Examining this perception, the present study investigated the impact of the gender of the protagonist on the audience preference, challenging the misconception that exists in the film industry globally that films starring females as protagonists are less commercially successful. The study conducted an online experiment of 434 participants who were assigned different movies starring male and female main characters and then completed the Bem Sex Role Inventory. They watched and read a summary of the movies and rated their expected pleasure of 24 randomly selected movie plots. Participants have also reported their previous exposure to the films. The study findings indicated that the anticipated pleasure of viewing female-dominant movies depended not on one’s sex but on gender identity. Interestingly, agentic (masculine-identified) participants were more likely to enjoy male-led films than feminine (communal-identified) participants were to enjoy female-led counterparts. The neutral participants noted no difference in their enjoyment. Additionally, increased familiarity with high-budget female-centered movies supplemented the significant correlation between female lead characters and expected enjoyment. In essence, The study challenges the stereotype that female-led films are less successful, suggesting that the industry should feature more diverse, empowered female characters for gender equality.